Description of Stolephorus horizon n. sp. from Fiji and Tonga, and redescription of Stolephorus scitulus (Fowler, 1911) (Teleostei: Clupeiformes: Engraulidae) - Harutaka Hata; Hiroyuki Motomura (Taxonomy, 2023)
The new anchovy Stolephorus horizon n. sp., described on the basis of 34 specimens collected from Fiji and Tonga, has been previously confused with Stolephorus indicus (van Hasselt, 1823) or Stolephorus scitulus (Fowler, 1911). However, the new species differs from both of the latter in having the pectoral fin without melanophores, and a unique range of gill rakers. A redescription of S. scitulus and an identification key of species previously identified as S. indicus are also provided.